Factors influencing home birth decisions among women in Al-Madinah, Saudi Arabia: A phenomenological study - sehimi, Ohood MA; Murad, Amal A.; Aloufi, Daniyah S. (African journal of reproductive health, 2025)
Home birth, as an element of maternity care, has been the subject of considerable debate regarding its safety and efficacy. Recent evidence suggests that for low-risk, multiparous women, planned home birth can be as safe as hospital birth, with reduced intervention rates and enhanced overall birth experiences. Additionally, economic assessments indicate that home birth represents a cost-effective alternative in specific contexts. However, in many high-income countries, including Saudi Arabia, home births remain rare due to prevailing socio-cultural attitudes, health system policies, and perceptions regarding the safety of home deliveries. This qualitative phenomenological study aims to explore the factors influencing the decision to choose home birth among reproductive-age women in Al-Madinah, Saudi Arabia. Semi-structured interviews were conducted with 25-30 participants to gather in-depth insights into their attitudes, beliefs, and experiences regarding home birth. The study findings highlight the interplay of cultural beliefs, socio-economic status, and prior childbirth experiences in shaping the preference for home delivery. Furthermore, the study sheds light on potential enablers, including improved midwifery services and health education, which could facilitate greater acceptance of home birth in Saudi Arabia. L'accouchement à domicile, en tant qu'élément des soins de maternité, a fait l'objet de nombreux débats quant à sa sécurité et à son efficacité. Des données récentes suggèrent que pour les femmes multipares à faible risque, un accouchement à domicile planifié peut être aussi sûr qu'un accouchement à l'hôpital, avec des taux d'intervention réduits et une expérience globale améliorée. De plus, des évaluations économiques indiquent que l'accouchement à domicile représente une alternative rentable dans certains contextes. Cependant, dans de nombreux pays à revenu élevé, dont l'Arabie saoudite, les accouchements à domicile restent rares en raison des attitudes socioculturelles dominantes, des politiques du système de santé et des perceptions concernant la sécurité des accouchements à domicile. Cette étude phénoménologique qualitative vise à explorer les facteurs influençant la décision d'accoucher à domicile chez les femmes en âge de procréer à Médine, en Arabie saoudite. Des entretiens semi-directifs ont été menés auprès de 25 à 30 participantes afin de recueillir des informations approfondies sur leurs attitudes, leurs croyances et leurs expériences concernant l'accouchement à domicile. Les résultats de l'étude mettent en évidence l'interaction entre les croyances culturelles, le statut socioéconomique et les expériences d'accouchement antérieures dans la détermination de la préférence pour l'accouchement à domicile. En outre, l'étude met en lumière des leviers potentiels, notamment l'amélioration des services de sages-femmes et de l'éducation sanitaire, qui pourraient favoriser une meilleure acceptation de l'accouchement à domicile en Arabie saoudite.